Desarrollo cognitivo diferencial e intervención psicoeducativa - Sylvia Sastre i Riba (Universidad de La Rioja, 2013)
We propose a revision of the concept of cognitive development from a neuroconstructivist point of view and their relations with the psicoeducational practices. From this point of view, we postule that we must adopt two guide-lines in order to know as large as possible the concept of development: 1. the differential one, and, 2. interaction (symmetrical or asymmetrical) as specific phenomenon in mental deficiency (concretely in Down's Syndrome ones) and high intellectual abilities (concretely, giftedness). We postulate the necessity of a psicoeducational intervention adjusted to their capabilities and necessities without inmovilisms.